2012
DOI: 10.6000/1927-520x.2012.01.02.11
|View full text |Cite
|
Sign up to set email alerts
|

Rhipicephalus (Boophilus) Microplus Ticks can Complete their Life Cycle on the Water Buffalo (Bubalus bubalis)

Abstract: Rhipicephalus (Boophilus) microplus is considered one of the most important ectoparasites of cattle worldwide. Due to the increase in the number of water buffaloes (Bubalus bubalis) in R. microplus-infested areas, this study was designed to determine whether these ruminants are able to sustain the complete tick life cycle. To this aim, a seven-month old water buffalo of the Mediterranean breed and a Holstein bovine of the same age, both tick-naïve, were infested with R. microplus tick larvae, and the parasitic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…This difference could be due to the river buffalo's wallowing behavior in mud and the survival mechanism of lice, that is, the ability to close respiratory orifices underwater. These findings concur with the research by Benitez [98], who conducted an assay with infection by the tick Rhipicephalus, which is considered the ectoparasite with the most significant negative impact worldwide on dairy cattle. This study used a Mediterranean buffalo calf and a Holstein calf of the same age under identical environmental conditions.…”
Section: Ectoparasitessupporting
confidence: 90%
See 1 more Smart Citation
“…This difference could be due to the river buffalo's wallowing behavior in mud and the survival mechanism of lice, that is, the ability to close respiratory orifices underwater. These findings concur with the research by Benitez [98], who conducted an assay with infection by the tick Rhipicephalus, which is considered the ectoparasite with the most significant negative impact worldwide on dairy cattle. This study used a Mediterranean buffalo calf and a Holstein calf of the same age under identical environmental conditions.…”
Section: Ectoparasitessupporting
confidence: 90%
“…Findings showed that the number of mature ticks on these animals corresponded, respectively, to 5.4% and 12% of the initial larvae detected, indicating resistance levels of 94.5% in buffaloes and 88% in cattle, respectively. Observations also found a marked inflammatory reaction in the adherence area of the ticks in the buffalo, a process not seen in the bovine because the buffalo's immune system was more reactive to the allergenic components in the saliva of the Rhipicephalus [98]. Another possible explanation could be that the buffalo's thicker skin limits the tick's capacity to anchor its hypostome.…”
Section: Ectoparasitesmentioning
confidence: 96%
“…Absent or attenuated clinical signs upon infection of these ruminants might have resulted from long coevolutionary adaptations with Rhipicephalus ticks and Babesia parasites. Their natural resistance to hemoparasites may be one of the reasons why these types of bovids are favored for meat and/or milk production in many tick-endemic regions (Jonsson et al 2008;Benitez et al 2012Benitez et al , 2018Florin-Christensen et al 2014).…”
Section: Babesia and Theileria Parasites In Cattlementioning
confidence: 99%
“…While the cattle tick R. microplus is also listed as one of the ectoparasites of water buffalo (32), this was rarely observed in water buffalo during our field collection. An experimental study confirmed the potential of water buffalo as hosts of R. microplus ticks (25). Thus, water buffalo may act as important reservoirs for the cattle tick and the pathogens that it transmits.…”
Section: Discussionmentioning
confidence: 63%